Ethnicity, disease severity, and survival in Canadian patients with primary biliary cholangitis. Issue 2 (15th March 2022) - Roberts, Surain B.; Hirschfield, Gideon M.; Worobetz, Lawrence J.; Vincent, Catherine; Flemming, Jennifer A.; Cheung, Angela; Qumosani, Karim; Swain, Mark; Grbic, Dusanka; Ko, Hin Hin; Peltekian, Kevork; Selzner, Nazia; et al.
Abstract: Background and Aims: We investigated associations between ethnicity, survival, and disease severity in a diverse Canadian cohort of patients with primary biliary cholangitis (PBC). Approach and Results: Patients with PBC were included from the Canadian Network for Autoimmune Liver Disease. Ethnicity was defined using a modified list adopted from Statistics Canada, and ethnicities with small samples were grouped. Clinical events were defined as liver decompensation, HCC, liver transplantation, or death. Clinical event–free and liver transplantation–free survival were analyzed using Cox regression. Trajectories of serum liver function tests were assessed over time using mixed‐effects regression. Health‐related quality of life was assessed using the Short Form 36, the PBC‐40 questionnaire, and the 5‐D Itch scale and analyzed using mixed‐effects regression. The cohort included 1538 patients with PBC from six sites and was comprised of 82% White, 4.7% Indigenous, 5.5% East Asian, 2.6% South Asian, and 5.1% miscellaneous ethnicities. Indigenous patients were the only ethnic group with impaired liver transplant–free and event‐free survival compared to White patients (HR, 3.66; 95% CI, 2.23–6.01; HR, 3.09; 95% CI, 1.94–4.92). Indigenous patients were more likely to have a clinical event before diagnosis (10%) than all other ethnic groups despite similar age at diagnosis. Indigenous patients presented with higher alkaline phosphatase, total bilirubin, and GLOBE scores than White patients; and these relative elevations persisted during follow‐up. Conclusions: Indigenous Canadians with PBC present with advanced disease and have worse long‐term outcomes compared to White patients. Abstract : image